PENDAMPINGAN PENYUSUNAN BUSINESS PLAN DENGAN TREN TECHNOPRENEURSHIP PADA SISWA/I SMK TECHNO MEDIA - Jelanti, Desi; Budiantini, Alya; Sutihat, Aat (Publika Citra Media, 2025)
A business plan is a framework that explains every part of the business that will be worked on from start to finish. And by including various events that must be anticipated if there are unwanted things that happen. So that a business plan is made by referring to conditions that are considered realistic or feasible to be implemented. Technopreneur can be simply interpreted as a technology enthusiast who has an entrepreneurial spirit and without an entrepreneurial spirit, a technology enthusiast will only be a technician who is less able to make the technology he is working on a source of life. This Community Service Activity aims to provide assistance in compiling a business plan with a technopreneurship trend for SMK Techno Media students with the provision of the will and creativity they have. The method developed in this activity is through socialization and assistance in compiling a business plan for students at SMK Techno Media in the Tangerang city area. This is based on a lack of understanding of the business plan, resulting in low awareness and difficulty in compiling a business plan, especially in the independence and creativity of students. So that with the activity of preparing a business plan for these students, it can provide insight, knowledge and skills for students at SMK Techno Media.